Gauging student learning attainment through seven variations of instructional screencast video / Sharmila Pachiyappan, Tan Wee Hoe and Ahmad Zamzuri Mohamad Ali - Pachiyappan, Sharmila; Tan, Wee Hoe; Zamzuri, Ahmad (UiTM Press, 2017)
This paper aims to investigate the effectiveness and the efficiency of a series of instructional screencast videos to learn a 3D modeling software. Seven variations of screencast video were developed using screen capturing software for self-paced learning among students who were taking a modeling course in the Bachelor of Design in Animation programme. A quasi-experiment was conducted in December 2014 with 35 students in a Malaysian public university. In the pre-test, all students were given similar tasks on modeling with lighting. The purpose of the pre-test was to determine if the students had prior knowledge and skills in 3D modeling. The result showed that none of the students could complete the given task, meaning that they were all fit for the quasi-experiment. Next, the students were randomly assigned to seven groups and each group of the students was given a variation of the screencast videos as treatment, while the control group was given a non-manipulated screencast video.